The use of plant material for enrichment of fresh juices by biologically active substances - Арпуль, Оксана Володимирівна; Усатюк, Олена Михайлівна; Жукова, Наталія Вікторівна (Technology audit and production reserves, 2015)
The fresh apple and orange juice with the use of aqueous extracts of non-traditional plant material such as peppermint, garden sage and lemongrass was developed for restaurants. It was chosen the simplest method of extraction such as maceration for obtaining extracts as a source of biologically active substances due to its ease of implementation at restaurants. The optimal process parameters (temperature, hydromodulus, time) which allow to obtain the extracts out of peppermint, garden sage and lemongrass with a pronounced and harmonious flavour were investigated. The food basis was chosen due to the popularity of fresh juices among the consumers of restaurants as well as availability and nutritional value of plant materials. The fresh apple and orange juice with the extracts of peppermint, garden sage and lemongrass had the original taste and aromatic profile. The biological value of the extracts of peppermint, garden sage and lemongrass was evaluated by the content of such antioxidant as vitamin C and the total antioxidant activity. The increasing of biological activity of the fresh juice with the aqueous extracts of plant materials was detected. It allows positioning the juice like a health drink.